2012
DOI: 10.5812/nephropathol.7518
|View full text |Cite
|
Sign up to set email alerts
|

Detection of immunoglobulins and complement components in formalin fixed and paraffin embedded renal biopsy material by immunoflourescence technique

Abstract: In conclusion, it is possible to establish the diagnosis in most cases of immune complex-mediated glomerular diseases with IF on paraffin embedded tissue specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The efficacy of IF-FFPE in renal biopsies has been studied in human medicine. In one study, three methods of AR (heating with a Tris buffer of unknown pH, heating with CB, and pronase digestion) were tested, and it was demonstrated that heating with Tris buffer was most effective, allowing the evaluation of ICs in renal biopsy specimens [ 9 ]. The efficacy of dual MW-heating methods using an EDTA buffer (pH 8.0) has also been previously reported [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of IF-FFPE in renal biopsies has been studied in human medicine. In one study, three methods of AR (heating with a Tris buffer of unknown pH, heating with CB, and pronase digestion) were tested, and it was demonstrated that heating with Tris buffer was most effective, allowing the evaluation of ICs in renal biopsy specimens [ 9 ]. The efficacy of dual MW-heating methods using an EDTA buffer (pH 8.0) has also been previously reported [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using human renal biopsies, routine IF-F and IF-FFPE have been compared in several reports [ 7 , 10 – 12 ]. Although one report suggested that IF-FFPE could not replace IF-F in renal biopsy assessment [ 12 ], most studies demonstrated good agreement between the two methods [ 7 , 9 11 ]. In this study, 12 biopsy samples were used to compare IF-FFPE after Try-30 and MW-TEB pretreatment to routine IF-F.…”
Section: Discussionmentioning
confidence: 99%
“…Because formalin fixation induces protein cross-linking, which generally blocks antigenicity, an antigen-retrieval step that allows for increased penetration of antibodies to the antigens “masked” by formalin fixation is required in IF-P. 5 , 6 This step involves incubating the paraffin sections with a proteolytic enzyme or heating the sections before incubation with fluorescein isothiocyanate–conjugated antibodies against Igs and complement components. Multiple proteolytic enzymes have been used in IF-P, including trypsin, 7 , 8 , 9 , 10 , 11 , 12 pronase E (protease XIV), 13 , 14 , 15 , 16 , 17 proteinase XXIV, 18 and proteinase K. 13 , 19 , 20 , 21 , 22 Successful results were also obtained by heat treatment with Tris or citrate buffers 15 and with dual microwave heating in EDTA antigen-retrieval solution. 23 In our laboratory, we use the pronase technique, which was originally described by Fogazzi et al.…”
Section: Methodologies Of Paraffin Immunofluorescencementioning
confidence: 99%
“… 37 (vi) The various IF-P techniques described are based on formalin fixation. 4 , 9 , 14 , 15 , 20 , 21 The performance characteristics of IF-P on non–formalin-based fixatives (Bouin, Duboscq-Brasil, and other fixatives) used in approximately 25% of renal pathology laboratories 38 , 39 are not known.…”
Section: Methodologies Of Paraffin Immunofluorescencementioning
confidence: 99%
“…Several laboratory techniques have been used to detect immunoglobulin complexes, such as ELISA for soluble complexes [8] and immunohistochemistry to trace their deposition in tissues [9]. Recently, flow cytometry is applied to detect immune complexes on the surface of erythrocytes.…”
Section: Introductionmentioning
confidence: 99%